Juggling friends and foes: Prime Minister Borissov's surprise survival in Bulgaria. Issue 3 (3rd July 2021) - Spirova, Maria; Sharenkova-Toshkova, Radostina
ABSTRACT: Prime Ministers (PMs) in Central and Eastern Europe have been relatively weak, although substantial variation in the survival both within and across countries exists. In Bulgaria, Boyko Borissov came to power in 2009 in most unfavourable situation: leader of a new party, he faced minority situation in parliament and had to cope with an ideologically heterogeneous coalition. Still, Borissov has become the longest serving PM in the country. This article examines the cabinet governance of Borissov I, II and III explores the PM's relationship with other parties inside and outside parliament as well as the mechanisms of cabinet management.